Preparation of low-cost nano and microcomposites from chicken eggshell, nano-silica and rice husk ash and their utilisations as additives for producing geopolymer cements. Issue 1 (2nd January 2020) - Tchakouté, H. K.; Tchinda Mabah, D. E.; Henning Rüscher, C.; Kamseu, E.; Andreola, F.; Bignozzi, M. C.; Leonelli, C.
ABSTRACT: This work aims to prepare low-cost nanocomposite and microcomposite with lower molar ratio CaO/SiO2 (0.4). Nano-silica, rice husk ash and calcined chicken eggshell have been used as silica and calcium sources. Metakaolin has been separately replaced by 0, 10 and 20 wt% of each composite in order to study their behavior on the properties of geopolymers. The hardener used is sodium waterglass from rice husk ash. The surface area of nano-silica and rice husk ash was 54.40 and 4.08 m 2 /g, respectively. The cumulative volumes of the control geopolymer, the ones containing 10 wt% of microcomposite and nanocomposite are 119.71, 89.92 and 110.49 mm 3 /g, respectively. The compressive strength of the control specimen is around 64.02 MPa. The one using 10 wt% of microcomposite was 68.97 MPa. It drops to 42.88 MPa when metakaolin was replaced by 20 wt % of microcomposite. Whereas the one using 10 wt% of nanocomposite was 30.03 MPa and it decreases to 26.05 MPa when metakaolin was substituted by 20 wt% of nanocomposite. It can be concluded that 10 wt% of microcomposite could be mixed to metakaolin for strength development and nanocomposite does not recommend to use as an additive for producing high strength of geopolymer cements.